THE CONSTRUCTION OF ORIENTALISM IN DAN BROWN’S DIGITAL FORTRESS - Widjajati, Ghassani Auliannnisa; Setiawan, Ikwan; Supiastutik, Supiastutik (Universitas Sebelas Maret, 2022)
This article studies orientalism constructed in the novel of Digital Fortress that is written by Dan Brown. Orientalism discourse appears in the literary works through narrative events and conversations of the Western and the Eastern. Ensei Tankado, a Japanese character, will be presented in this study in the lens of Western. The aim is to explore orientalism discourse in the novel to get an understanding of the ideology interest as part of the Western power. Theory of Orientalism by Edward Said is applied in this study. It modifies Foucauldian discourse theory and Gramscian hegemony. The four concept of Orientalism discourse including political power, intellectual power, cultural power and moral power will be used in this study. How the Eastern subject is positioned by the Western in Digital Fortress becomes the focus. Japanese and the United States in the novel can be related to the contextual condition that cultural domination and hegemony still occur between Japan-USA since World War II. Orientalism in the literary works is a new imperialism. The goal of this study is to reveal that the novel brings cultural domination.